The prevalence and outcomes of pre‐admission vitamin D levels in the management of proximal femur fractures - Aysha Rajeev; Connor Hunter; Saurav Krishnan; Atta Ullah; George Koshy; Gateshead Health Foundation NHS Trust (Aging Medicine)
Abstract Objectives The prevalence of low Vitamin D levels (<30 nmol/L) is about 15.7% globally. The aim of this study was to examine the prevalence of vitamin D deficiency in elderly patients with fragility fractures of the hip by estimating 25‐hydroxyvitamin D levels and to assess whether low vitamin D levels at the time of admission affect functional outcomes at 3 months and mortality at 28 days and 1 year. Methods We conducted a retrospective study of all patients admitted with a fracture of the neck of the femur between January 2018 and March 2022. Data were obtained from the National Hip Fracture Database (NHFD) and Medway software. A total of 1440 patients were included. Patient demographics, including age, sex, fracture pattern, vitamin D levels at the time of admission, functional status at 120 days, and mortality at 1 month and 1 year, were analyzed. Results The average age of the patients was 81.91 years (range 60–108). Of the patients, 1009 (70%) were female and 431 (30%) were male. Vitamin D levels were low in 796 patients (55.3%). Mobility significantly declined in patients with vitamin D deficiency within 3 months after surgery for proximal femur fractures. The 28‐day and one‐year mortality rates were 6.7% and 30.3%, respectively, in patients with low vitamin D levels, compared to 4.7% and 22.3% in those with normal levels. Patients with low vitamin D levels at the time of admission had higher mortality rates at both 28 days and 1 year compared to those with normal levels. Conclusion Our study demonstrates that low vitamin D levels at the time of admission for proximal femur fractures are associated with poorer functional mobility and higher perioperative and 1‐year mortality rates.